Patient-directed vs. fixed-volume PEG for colonoscopy preparation: a randomized controlled trial. Issue 2 (25th May 2022) - Zhang, Jixiang; Jia, Xuemei; Guo, Yuanmei; Jiang, Haotian; Hu, Jiaming; Wang, Siwei; Huang, Binglu; Su, Wenhao; Liu, Jun; Wang, Xiaoli; Dong, Weiguo
ABSTRACT: Background: Individualization using different volumes of polyethylene glycol is widely regarded as the optimal solution for bowel preparation, while the patient-directed regimen we propose may serve as a reliable individual solution. This study aimed to assess the efficacy, safety, and satisfaction of bowel preparation with a patient-directed regimen. Methods: Patients in the fixed-volume group ingested the same amount of PEG, while those in patient-directed group ingested different amount according to stool consistency or stool water content. Results: After filtering by exclusion criteria, 428 individuals in the fixed-volume group and 103 in the patient-directed group were successfully enrolled and analyzed. Eighty-three (80.6%) individuals in the patient-directed group had a reduced polyethylene glycol volume. There was no significant difference in the bowel preparation efficacy between the two groups (90.0% vs. 90.3%, χ² = 0.01; p = 0.918). Patients in the patient-directed group complained of fewer adverse effects (53.0% vs. 36.9%, χ² = 8.655; p = 0.003), especially vomiting (13.6% vs. 1.0%, χ² = 13.304; p < 0.001). Regarding comfort during bowel preparation, the degree of comfort was not significantly different between groups. Furthermore, the willingness rate for further colonoscopy in the patient-directed group was significantly higher than that in the fixed-volume group (90.3% vs. 77.1%, χ² = 8.912; p < 0.05). Multivariable logistic regression analysis showed that the body mass index served as an independent factor impacting quality of bowel preparation with the patient-directed regimen (OR 1.16, 95% CI 1.00–1.34; p = 0.043). Conclusions: Without decreasing the bowel preparation efficacy, the patient-directed regimen increased the safety and satisfaction of bowel preparation and is expected to be a regular and individual solution for bowel preparation. Individuals with a lower body mass index are more likely to undertake this new regimen. Trial registration number: ChiCTR1900022072 at ChiClinicalTrials.gov